Mixotrophic Growth of Chlorella sorokiniana on Acetate and Butyrate: Interplay Between Substrate, C:N Ratio and pH - Lacroux, Julien; Seira, Jordan; Trably, Eric; Bernet, Nicolas; Steyer, Jean-Philippe; van Lis, Robert (Frontiers in Microbiology, 2021)
Microalgae can be cultivated on waste dark fermentation effluents containing volatile fatty acids (VFA) such as acetate or butyrate. These VFA can however inhibit microalgae growth at concentrations above 0.5 – 1 gC.L-1. This study used the model strain Chlorella sorokiniana to investigate the effects of acetate or butyrate concentration on biomass growth rates and yields alongside C:N:P ratios and pH control. Decreasing undissociated acid levels by raising the initial pH to 8.0 allowed growth without inhibition up to 5 gC.L-1 VFAs. However, VFA concentration strongly affected biomass yields irrespective of pH control or C:N:P ratios. Biomass yields on 1.0 gC.L-1 acetate were around 1.3-1.5 gC.gC-1 but decreased by 26-48% when increasing initial acetate to 2.0 gC.L-1. This was also observed for butyrate with yields decreasing up to 25%. This decrease in yield in suggested to be due to the prevalence of heterotrophic metabolism at high organic acid concentration, which reduced the amount of carbon fixed by autotrophy. Finally, the effects of C:N:P on biomass, lipids and carbohydrates production dynamics were assessed using a mixture of both substrates. In nutrient replete conditions, C. sorokiniana accumulated up to 20.5% carbohydrates and 16.4% lipids while nutrient limitation triggered carbohydrates accumulation up to 45.3%.